Development of an Automated Temperature Control System for Optimized Chocolate Tempering: Pengembangan Sistem Kontrol Suhu Otomatis untuk Optimasi Tempering Cokelat - Astryani, Dita; Rakhmadi, Frida Agung (Sunan Kalijaga Journal of Physics, 2024)
This study presents the design and development of a temperature control system for the chocolate tempering process using an RTD PT1000 sensor and an Arduino Uno microcontroller. Sensor characterization yielded a linear transfer function V = −0.0037T+3.4085V, with a strong correlation (r = −1.054), sensitivity of −0.0037 V/°C, and repeatability of 99.4%. The control system was programmed to maintain temperature within an optimal range by switching the heating element off above 53 °C and on below 40 °C. System testing across 10 cycles demonstrated a success rate of 97.7%, confirming the effectiveness and reliability of the system. The results suggest that the proposed solution can improve temperature stability and efficiency in small-scale chocolate processing applications.